Evaluation of the Effectiveness of MGMP Activities in Improving the Ability of Teachers to Write Scientific Papers in MAN 2 Tidore Islands City: Evaluasi Efektivitas Kegiatan MGMP dalam Meningkatkan Kemampuan Guru Menulis Karya Ilmiah di MAN 2 Kota Tidore Kepulauan - Adam, Adiyana; Limatahu, Kartini; Fitrianto, Arif Rahman; Junaedi, Erina; Masuku, Mardiani; R Husen, Rinelsa (Institut Riset dan Publikasi Indonesia, 2025)
The Subject Teacher Consultation (MGMP) program plays a crucial role in enhancing teachers' professionalism, particularly in scientific writing. This study evaluates the effectiveness of MGMP activities at MAN 2 Tidore Islands City in improving teachers' scientific writing skills. Using a Community-Based Research (CBR) approach, this study actively involved teachers in training and mentoring sessions. Survey results indicate that most participants found the training relevant to their needs, showing a significant improvement in their writing skills. The evaluation method, using online surveys, enabled quick and accurate analysis. The key factors contributing to the program's success were the community-based approach, mentoring support, and the relevance of the training materials to teachers' needs. In conclusion, the pre-test dan post-testMGMP program effectively enhances teachers' scientific writing skills. The study recommends further training with more intensive mentoring sessions to help teachers publish their research in relevant academic journals.